The dislocation of teaching and research and the reconfiguring of academic work (UCL Press, 2012)
The relationship between teaching and research is a touchstone in thinking about higher education. However, the last 40 years has seen the 'dislocation' of these core academic activities as a result of policy and operational decisions to distinguish the way they are funded, managed, assessed and rewarded. The activities of 'teaching' and 'research' are also disintegrating and the roles fragmenting, which, paradoxically, is allowing their reintegration in novel and innovative ways. However, this process cannot, ultimately, be successful without the fundamental reconfiguration of academic work to meet the needs of a different student cohort and a changing society and economy.